Thermodynamic analysis of syngas production and carbon formation on oxidative steam reforming of butanol. (12th January 2016) - Horng, Rong-Fang; Lai, Ming-Pin; Chiu, Wei-Cheng; Huang, Wei-Chih
Abstract: Theoretical calculations of chemical equilibrium were adopted to explore the syngas production of oxidative steam reforming of butanol (OSRB). The results indicated that when the H2 O/C4 H9 OH molar ratio was 3 and the O2 /C4 H9 OH molar ratio was 1.5, the thermal neutrality temperature reached 602 °C, generating a corresponding H2 yield of 59.3%, a CO yield of 39.5%, and reforming efficiency of 65.1%. Additionally, when the OSRB was at moderate temperatures (400–800 °C), adding an appropriate amount of O2 effectively inhibited coke formation and exerted only a minor effect on butanol reforming efficiency. The analysis of the coking boundaries indicated that at the same H2 O/C1 molar ratio, alcohol fuels with higher carbon numbers (butanol > ethanol > methanol) produced higher degrees of coke formation. However, if OSRB was used, the amount of H2 O and O2 addition was able to be controlled to inhibit coke formation and reduce the coke formation zone considerably. Highlights: Syngas production and carbon formation were calculated by thermodynamic analysis. The syngas production of oxidative steam reforming of butanol (OSRB) was performed. The carbon formation in the alcohol reforming reactions was discussed. The reforming efficiency is 93.6% at optimal OSRB parameters.